1991
DOI: 10.1002/bit.260380920
|View full text |Cite
|
Sign up to set email alerts
|

Large‐Scale, High‐density freezing of hybridomas and its application to high‐density culture

Abstract: Large-scale, high-density freezing of hybridomas was studied to apply frozen cells t o start high-density culture.We showed here that hybridomas can be frozen at 1.5 x lo8 cells/mL, without decrement in viability and proliferating activity. Blood transporting bags were used for large-scale freezing to store 25 mL of cell suspension with a cell density, 1.5 x lo8 cells/mL. The number of cells stored in a bag (3.0 x lo9 cells) was enough to start a high-density culture at a 10 times higher cell density (6.0 x lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 11 publications
0
20
1
Order By: Relevance
“…This is in contrast to the findings of Ninomiya et al (1991) who reported that high-density seeding at 6 Â 10 6 cells/mL of hybridoma cells after cryopreservation shortened the lag period before IgM production started. However, the proliferating rate of the high-density seeded hybridoma cells was not improved, which shows that growth rate and productivity are not necessarily proportionally related to each other.…”
Section: Increased Freezing Density and Lowered Me 2 So Concentrationcontrasting
confidence: 85%
See 1 more Smart Citation
“…This is in contrast to the findings of Ninomiya et al (1991) who reported that high-density seeding at 6 Â 10 6 cells/mL of hybridoma cells after cryopreservation shortened the lag period before IgM production started. However, the proliferating rate of the high-density seeded hybridoma cells was not improved, which shows that growth rate and productivity are not necessarily proportionally related to each other.…”
Section: Increased Freezing Density and Lowered Me 2 So Concentrationcontrasting
confidence: 85%
“…High-density freezing (from 20 to 40 Â 10 6 to 150 Â 10 6 cells/mL) in the presence of 10% Me 2 SO have also been performed successfully with BHK, CHO-S (Heidemann et al, 2002) and hybridoma (Ninomiya et al, 1991) cell lines. The exact mechanism of the protective properties of keeping the cells firmly packed during the freezing/thawing process is currently not known.…”
Section: Increased Freezing Density and Lowered Me 2 So Concentrationmentioning
confidence: 96%
“…This has been driven primarily by their ease of use and elimination of resource-intensive cleaning and sterilization procedures needed for more traditional glass or stainless steel vessels. Several groups have reported successful use of such disposable technologies for preparation of clinical materials under GMP conditions (Hami et al, 2004), for production of monoclonal antibodies (Ling et al, 2003) and cryostorage (Ninomiya et al, 1991). These disposable vessels typically consist of hydrophobic polymer films such as polyethylene (PE) and ethyl vinyl acetate (EVA).…”
Section: Introductionmentioning
confidence: 99%
“…The cryobags are designed to contain enough cells to inoculate the bioreactor directly without the necessity of any DMSO removal and the need of any additional small-scale culture vessels (Tflasks, spinners, roller bottles, etc.). The feasibility to use large-volume cryobags for cryopreservation in long-term storage conditions have been demonstrated in the past (Heidemann et al, 2002;Junker et al, 2002;Ninomiya et al, 1991;Regidor et al, 1998;Regidor et al, 1999). For example, Regidor et al 1998 reported stability data of umbilical cord blood preserved in blood transporting bags for more then 7 years.…”
Section: One-step Inoculation Procedure-a Relative Novel Approachmentioning
confidence: 94%
“…Studies have demonstrated that the use of a large volume in combination with high density enables freezing and storage at about 100 times higher cell numbers than in the conventional case (2 mL cryovials). Cryobags successfully used in blood cell banking are used as a large-volume cryocontainer in place of conventional cryovials (Junker et al, 2002;Ninomiya et al, 1991;Regidor et al, 1999).…”
Section: Seed-train Expansionmentioning
confidence: 98%